Sensors: Sulfonated Mesoporous Silica as Proton Exchanging Layer in Solid‐State Organic Transistor (Adv. Electron. Mater. 12/2017). (11th December 2017) - Yambem, Soniya D.; Timm, Jana; Weiss, Morten; Pandey, Ajay K.; Marschall, Roland
Abstract : The ability to detect protons with electronic devices is crucial for developing electronics with advanced functionalities for interfacing and/or integrating electronics with many biological systems. In article1700316, Soniya D. Yambem and co‐workers report an all‐solid‐state and low‐voltage‐operating electronic device to detect protons by using proton‐conducting nanoparticles in an organic thin‐film transistor.